Productivity and Natural Disease Resistance Potential of Free-ranging Local Chicken Ecotypes in Tanzania - Msoffe, P.L.M.; Mtambo, M.M.A.; Minga, U.M.; Gwakisa, P.S.; Mdegela, R.H.; Olsen, J.E. (2002)
This study was carried out to investigate the productivity and the natural disease resistance potential of free-ranging local chickens in Tanzania. A total of 84 adult free-ranging local chicken ecotypes were studied, namely: Mbeya, Morogoro-medium, Ching’wekwe, Kuchi and Singamagazi. Adult body weight, body length, shank length and egg weight were assessed and compared. Average body weight for hens and cocks was 1441g (800 to 2,300g) and 2261g (1000 to 3500g), respectively. Egg weight averaged 41.6g (27 to 72g). Mean body length for hens and cocks was 21.6cm (17 to 26cm) and 24.6cm (21 to 29cm), respectively, and mean shank length 9.7cm (7 to 12cm) and 12.7cm (8.5 to 15cm), respectively. Between ecotypes significant differences were seen in the above parameters. The disease resistance potential was tested on 10 offspring of each ecotype, excluding the Mbeya. Twenty chickens (five from each of the four ecotypes) aged 12 weeks were inoculated with Newcastle disease virus while another 20 aged 20 weeks were inoculated with Salmonella gallinarum. Five chickens per group that were not challenged were used as controls. Following oral, ocular and nasal drop inoculation with Newcastle disease virus, the chickens developed clinical signs of Newcastle disease as from day three after infection. Mortality started on day five after infection, and all but one chicken were dead by day seven after infection. The 20 chickens, infected orally with S. gallinarum, showed clinical signs of fowl typhoid on day three after infection. Mortalities started on day seven after infection and by day 12 after infection 13 chickens had died. Seven birds survived without visible signs of the disease, including all five from the Kuchi ecotype and one each of the Morogoro-medium and Ching’wekwe ecotypes. At necropsy enlarged and congested liver and spleen, and catarrhal enteritis of the small intestines were seen. The surviving birds were sacrificed on day 14 after infection. Neither the sacrificed surviving birds nor the controls showed the above necropsy picture. It was concluded that free-ranging local chicken ecotypes in Tanzania differ in both productivity and disease resistance potential.